2019
DOI: 10.1002/mpr.1809
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, dimensionality and clinical relevance of self‐disturbances and psychotic‐like experiences in Polish young adults: a latent class analysis approach.

Abstract: Objectives We aimed to investigate latent classes of psychotic‐like experiences (PLEs) and self‐disturbances (SD) and to explore mutual overlapping between derived subgroups. Further, our goal was to investigate class membership relationship with an exposure to childhood trauma and different psychopathological factors such as cognitive biases, depression, insomnia, psychiatric diagnosis and lifetime suicidality. Methods Participants consist of 3167 non‐clinical adults. We performed two latent class analyses (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
(113 reference statements)
2
6
0
Order By: Relevance
“…Lower scores were also observed in the Trusting sub-scale, indicating that individuals in the High-Risk group were less likely to consider their body as a safe place. While there are no previous studies that have directly explored trust in one's own body across the psychosis spectrum, our results appear to be consistent with studies that have reported coenaesthesia and abnormal body perception in healthy individuals who appear to be prone to psychotic experiences (Gawęda et al, 2019;Germine et al, 2013;Graham et al, 2015;Pionke et al, 2020), and among individuals with schizotypal personality (Van Doorn et al, 2018). Similar results have also been observed among help-seeking and clinical samples including individuals at clinical high risk for psychosis (Nelson et al, 2012), and patients with schizophrenia (Klaver & Dijkerman, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Lower scores were also observed in the Trusting sub-scale, indicating that individuals in the High-Risk group were less likely to consider their body as a safe place. While there are no previous studies that have directly explored trust in one's own body across the psychosis spectrum, our results appear to be consistent with studies that have reported coenaesthesia and abnormal body perception in healthy individuals who appear to be prone to psychotic experiences (Gawęda et al, 2019;Germine et al, 2013;Graham et al, 2015;Pionke et al, 2020), and among individuals with schizotypal personality (Van Doorn et al, 2018). Similar results have also been observed among help-seeking and clinical samples including individuals at clinical high risk for psychosis (Nelson et al, 2012), and patients with schizophrenia (Klaver & Dijkerman, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…The presence of PLEs can impact daily functioning and is considered indicative of an increased risk to develop psychosis (Bukenaite et al, 2017;Fisher et al, 2013;Kaymaz et al, 2012;Mossaheb et al, 2012). Similar to patients with psychosis, studies conducted on this population have highlighted abnormal self-and bodily experiences, sleep dysfunction, and impaired social cognition (Andorko et al, 2017;Barragan et al, 2011;Gawęda et al, 2019;Graham et al, 2015;Pionke et al, 2020). Abnormal functioning of the insular cortex has also been reported (Papanastasiou et al, 2020), suggesting that interoception is likely an area worthy of investigation.…”
mentioning
confidence: 89%
“…LCA classified the sample into 3 classes: low, intermediate and high endorsement of HLEs, providing evidence for their existence on a continuum (van Os and Reininghaus, 2016). The three classes differed quantitatively with the largest group being the low endorsement group (48%), similar to Pionke et al's (2019) study. Class 3 or the high endorsement group was the smallest supporting Linscott and Van Os (2013) hypothesis that the most severe class is less frequent in the general population.…”
Section: Discussionsupporting
confidence: 85%
“…Latent class analysis (LCA) helps to identify subgroups in the larger population that have probabilistically similar endorsement profiles for PLEs, and to understand the pattern of their experiences (Gale et al, 2011). Some studies have found a three class solution of PLEs in the general population using LCA (Gale et al, 2011;Mamah et al, 2013;Pionke et al, 2019), while others have found a four class solution (Pignon et al, 2018;Shevlin et al, 2007) with differing degrees of PLEs endorsement ranging from a 'normative' class (almost no psychotic symptoms) to a 'psychosis' class (very high prevalence of all psychotic symptoms). These studies have clinical relevance as greater the prevalence of PLEs in a subgroup, greater is the prevalence of comorbid psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SD can be considered more broadly, not only as phenomena that constitute the core of schizophrenia but also as self-experiences present on a continuum of a varying intensity [32]. This seems to be confirmed by studies revealing their occurrence in non-clinical populations where they correlate with PLEs [33][34][35] and schizotypy [36,37]. Some authors also point to the need to search for these types of SD that, apart from their intensity, would distinguish SSD from other disorders [28].…”
Section: Introductionmentioning
confidence: 94%